PENGARUH UMUR, JUMLAH TANGGUNGAN KELUARGA, LUAS LAHAN, PENDIDIKAN, JARAK TEMPAT TINGGAL PEKERJA KE TEMPAT KERJA, DAN KEUNTUNGAN TERHADAP CURAHAN WAKTU KERJA WANITA TANI SEKTOR PERTANIAN DI DESA TAJUK, KEC. GETASAN, KAB. SEMARANG - Widyawati, Retno Febriyastuti; Pujiyono, Arif (Diponegoro Journal of Economics, 2013)
The agricultural sector in Semarang district has the third contribution in Gross Regional Domestic Product, but it became the most high-sector employment women. This indicates that employment opportunities for women are wide open, so the more you enter the job market. This raises the dual role of the female worker as a housewife as well as workers. This study aims to analyze the factors that affect the flow of time working women farmers in the study village Tajuk, district. Getasan, Semarang.Method of data analysis used in this study is a model of multiple linear regression or OLS with outpouring of work time as the dependent variable, while age, number of dependents, land area, level of education, distance of residence of workers to work, profit as an independent variable.Results of the analysis showed the variables age, number of dependents, land area, the distance of residence to the workplace, and profit a positive and significant effect of the outpouring of women farmers working time. Education variables and no significant negative effect on women farmers outpouring of work time.